Chromozone: aplikasi pemantau kadar nadi sistem ios semasa senaman menggunakan sistem kod warna universal (Chromozone: iOS-based exercise heart rate application using universal colour-coding system) / Adam Linoby ...[et al.] - Linoby, Adam; Kusrin, Jamiaton; Asraff, Muhammad Iskandar; Rodzi, Muhammad Azamuddin; Zaki, Sufyan; Hasan, Hosni (Universiti Teknologi MARA, 2020)
The conventional heart rate monitor is usually developed with a numeric digital display. This numerical view is obviously not practical to be used during exercise. In this study, the iOS-based mobile application, called Chromozone, was developed to monitor heart rate using the universal colorcoding system. The heart rate monitor during the exercise is designed to notify the exercise intensity information to users using the three universal color-coded (i.e. green zone: optimal heart rate; yellow zone: heart rate lower than the optimal zone, and red zone: heart rate higher than the optimal zone). Chromozone is programmed to display uniform colors across the smart phone display, which allows users to easily be informed in regards to the state of exercise intensity. The transfer of heart rate data from the chest transmitter to Chromozone application is designed to use Bluetooth Low Energy (BLE) system technology. The heart rate data is then processed by the application to determine the intensity range of exercise training heart rate based on the user's personal input (i.e. age, gender, fitness levels and training objective). Preliminary analysis found that Chromozone application is effective in delivering real-time exercise intensity heart rate. Chromozone could potentially help athletes, active individuals and clinical populations to monitor and regulate their workout training regime in a more effective and safer manner.